Wyndham Halswelle and the 1908 Olympic 400 metres final, the most controversial race in Olympic history?. Issue 2 (3rd April 2018) - Harris, Luke; Adams, Iain
ABSTRACT: One of the central narratives of the 1908 Olympic Games is the intense Anglo-American acrimony which culminated in the nadir of their sporting relations. One of the major controversies involved the 400 metres final which featured Halswelle, a British athlete, and three Americans – Carpenter, Robbins and Taylor. The final was declared void after Carpenter obstructed Halswelle and was disqualified. In protest the Americans withdrew Robbins and Taylor from the re-run and Halswelle won the gold medal unopposed. This paper explores the 400 metres final from the perspective of the British athlete Wyndham Halswelle utilising his diaries, photo albums, scrapbooks and the papers of his elder brother, Gordon. Serendipitously, the continual digitisation of newspapers also gave further insight into allegations of illegal team tactics by Carpenter and Robbins in the initial race. The article then further exploits these resources to develop a case study of Halswelle as an elite early-twentieth-century British amateur athlete. Differences in ideas of the amateur athlete ideal are often identified as an underpinning cause of international squabbling at the IV Olympiad and may have led to Halswelle's decision to retire after the games at the age of 26 while still improving his performances.